Area deprivation amplifies racial inequities in premature mortality: Analysis of 242, 667 deaths in Washington State, USA 2011-15. (January 2020) - Monsivais, Pablo; Amiri, Solmaz; Denney, Justin T.; Amram, Ofer
Abstract: Racial and socioeconomic inequalities in health are consistently reported, but less is known about the interplay between racial and deprivation-related inequities. We used geographically-localized data on all deaths recorded in Washington state 2011 to 2015 (n = 242, 667 decedents) and multi-level regression models to examine premature (<65 years) mortality by race and neighborhood deprivation separately and in combination. White versus non-white inequities in premature mortality did not vary substantially with increasing levels of deprivation. However, most non-white races from deprived neighborhoods had odds of premature mortality between three and eight times that of more-affluent whites. These findings may reflect the compounding of disadvantage stemming from social and environmental risk factors. Highlights: In the United States, race and deprivation are well-known risk factors for premature mortality. Less is known about the interplay between race and neighborhood deprivation in relation to premature mortality. Analysis of 242, 000 deaths in WA state confirms race and area deprivation are independently associated with premature death. The combination of non-white race with higher area deprivation amplified odds of premature mortality. Apparent racial inequities in mortality may be amplified by social and environmental risk factors present in deprived areas.